Impact of ICT on service management in the Zimbabwean public sector: a case of Zimbabwe National Road Administration (ZINARA) - Duve, Richard; Tambudzai, Zachary (Midlands State University, 2016)
Paper prepared for the Midlands State University 1st International Research Conference: Driving Socio-Economic Development through Value Addition and Sustainable use of Resources, held at Elephant Hills Resort, Victoria Falls, Zimbabwe 14-16 July 2015